Curiosity dalam kehidupan sehari-hari - Wardah Arum Bayuningrum (Universitas Muhammadiyah Malang, 2021)
One important thing to achieve the best academic results, one important thing is needed, namely curiosity. Curiosity isrequiredtoobtainnewinformationandisconsideredthedrivingforceinvolvedinmakingnewconnectionsbetween ideas, perceptions, concepts, and representations. This article aims to review research on the role of curiosity in everyday life. We review conducted on 20 research results published in international journals between 2000 and 2017. The review results show that curiosity has an essential and consistent role in inﬂuencing a person’s life positively or negatively. Someone who has a high curiosity aspect, then that person will explore information, willingness and desire to search for information, have adventures with information, and be more active in asking other people.